Multi-collector 40Ar/39Ar dating of microtektites from Transantarctic Mountains (Antarctica): A definitive link with the Australasian tektite/microtektite strewn field - Di Vincenzo, Gianfranco; Folco, Luigi; Suttle, Martin D.; Brase, Lauren; Harvey, Ralph P. (Geochimica et Cosmochimica Acta, 2021)
Microtektites represent high-velocity/distal meteorite impact ejecta. Demonstrating that microtektites found at several locations throughout East-Antarctica consist of a homogeneous class of geological objects belonging to the Australasian tek- tite/microtektite strewn field is fundamental to define the actual extent of the largest and youngest known tektite field on Earth produced by an asteroidal impact $0.8 Ma ago. This study presents new 40Ar/39Ar analyses performed by multi- collector noble gas mass spectrometry on individual microtektites from two key locations in the Transantarctic Mountains: Miller Butte, in northern Victoria Land, and Mount Raymond, over 1,000 km further south, in the Grosvenor Mountains. Results indicate that particles are heavily contaminated by at least one extraneous Ar component, which is not correlated with size nor with bulk chemical composition, and precludes a straightforward interpretation of 40Ar/39Ar data. Analysis of data from step-heating and total fusion analyses in three-isotope correlation diagrams yielded indistinguishable isochron ages from the two locations, with a combined isochron average of 800 ± 89 ka (95% confidence level). These age results improve by more than one order of magnitude previously published 40Ar/39Ar age determinations and improve by $4 times a previous fission track date, thus providing conclusive evidence that microtektites found throughout the Transantarctic Mountains of Antarc- tica belong to a single source – the Australasian field. This study strengthens the southward extension of the Australasian field ($4,000 km southward with respect to Australasian microtektites recovered at lower latitudes from deep sea sediments), thus implying a launch distance of nearly 12,000 km from the putative impact location in Indochina. From a broad perspective, results also reveal a contrasting behavior between microtektites from the Transantarctic Mountains, highly contaminated by extraneous Ar, and Australasian macroscopic tektites, weakly or negligibly ...